Internet User Research in Product Development: rapid and low cost initial research for Information - Shekar, Aruna (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Small to Medium Enterprises (SMEs) face enormous financial risks when developing new products. A key element of risk minimisation is an early emphasis on gathering information about the end users of the product quickly. SMEs are often overwhelmed by the prospect of expected research costs, lack of expertise, and financial pressures to rush to market. Too often the more conventional path is chosen, whereby a solution is, developed and tested in the market to “see if it sticks”. Such methodologies are less effective and subject the SME to increased financial risk. This study demonstrates how SMEs can make use of freely available internet resources to reproduce aspects of more sophisticated customer research techniques. Internet resources such as the YouTube and Forums enable SMEs to research customers rapidly, and in a cost effective manner. This study examines New Zealand SMEs and presents two case studies to support the use of modern web-based user research in new product development.